2021
DOI: 10.1002/acr2.11341
|View full text |Cite
|
Sign up to set email alerts
|

Patient Empowerment and Associations with Disease Activity and Pain‐Related and Lifestyle Factors in Patients With Rheumatoid Arthritis

Abstract: Background. Empowerment is important to patients with rheumatoid arthritis (RA) because most care is in the form of self-management. The aim was to study levels of empowerment and associated variables in patients with RA and to investigate longitudinal clinical data in patients with low and high empowerment.Methods. A postal survey was sent in 2017 to patients with RA from the BARFOT (Better Anti-Rheumatic Pharmacotherapy) cohort that included questions about disease activity, pain-related factors, lifestyle h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
1
7
0
4
Order By: Relevance
“…Existe una relación moderada positiva entre el empoderamiento y la CV de las personas adultas con EC en El Salvador (rho = 0,444; p = 0,007) (Figura 1). 17 [13,25] 19 [18][19][20] 0,394 17 [7, 19 [15][16][17][18][19]5] 17 [14][15][16][17][18] 0,624 15 [14][15][16][17][18] 19 [11][12][13][14][15][16][17][18][19][20] 17 [14-18, con artritis reumatoide es comparable con el de otras enfermedades crónicas y agregó que el nivel de empoderamiento está asociado a factores relacionados con la CV, la función física y los niveles de actividad física. Las personas con un nivel bajo de empoderamiento reportaron un nivel también bajo de CV.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Existe una relación moderada positiva entre el empoderamiento y la CV de las personas adultas con EC en El Salvador (rho = 0,444; p = 0,007) (Figura 1). 17 [13,25] 19 [18][19][20] 0,394 17 [7, 19 [15][16][17][18][19]5] 17 [14][15][16][17][18] 0,624 15 [14][15][16][17][18] 19 [11][12][13][14][15][16][17][18][19][20] 17 [14-18, con artritis reumatoide es comparable con el de otras enfermedades crónicas y agregó que el nivel de empoderamiento está asociado a factores relacionados con la CV, la función física y los niveles de actividad física. Las personas con un nivel bajo de empoderamiento reportaron un nivel también bajo de CV.…”
Section: Resultsunclassified
“…Las personas con un nivel bajo de empoderamiento reportaron un nivel también bajo de CV. 13 La correlación entre empoderamiento y CV también se confirmó en un estudio transversal en Portugal en personas con enfermedad reumática. El estudio corroboró que el empoderamiento se relaciona positiva y significativamente con todas las dimensiones de la CV.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Theoretically, a tight control regime could increase the patient's sense of security and confidence in the treatment, which could have a positive impact on their perception of pain (Edwards et al., 2016). A recent study has shown lower pain and better physical function in patients who report greater empowerment (Larsson et al., 2021). Great demands are made on the patient's ability to manage one's own symptoms in rheumatological care.…”
Section: Discussionmentioning
confidence: 99%
“…The work of patient organisations has sought to highlight that any individual with moderately active disease may now benefit from the newly available biologic therapies, and they have encouraged patients to contact their rheumatology department for a review. Patient empowerment and engagement to take an active role on a treatment plan is essential [ 40 ]. This is facilitated by the use of patient-reported outcome measures (PROMs) for assessment of the aspects of life most impacted by RA.…”
Section: Introductionmentioning
confidence: 99%